Characterization Of Bioethanol From Cassava As A Fuel In Gasoline Engines - Muhammad Ihsan; Yolli Fernanda; Arwizet K; Andre Kurniawan (Jurnal Vokasi Mekanika (VoMek), 2025)
The energy demand in Indonesia continues to increase, particularly in the transportation sector, which remains highly dependent on fossil fuels such as gasoline. This dependency causes several issues, including the depletion of fossil fuel reserves and the rise of greenhouse gas emissions that negatively impact the environment. One potential solution to address these challenges is the development of bioethanol as a renewable and environmentally friendly alternative fuel. Bioethanol can be produced from starchy materials, one of which is white cassava (Manihot esculenta), known for its high productivity and wide availability in Indonesia. The production process of bioethanol consists of several stages, including liquefaction, fermentation, and distillation, where fermentation temperature plays a crucial role in determining the ethanol yield. Previous studies have shown that variations in fermentation temperature significantly influence the efficiency of bioethanol production. This study aims to characterize bioethanol produced from cassava fermentation at various temperature variations and to evaluate its potential as a fuel for gasoline engines. The results are expected to contribute to the improvement of bioethanol production efficiency and to promote cassava utilization as a renewable energy source in supporting national energy sustainability.